IMPLEMENTATION OF ECONOMIC ORDER QUANTITY (EOQ) ON INVENTORY EFFICIENCY IN PT. HEALTH TODAY INDONESIA - Al Adawiyah; Khoirul Umam (STIE Mandala Jember, 2020)
Optimal inventory management is one of the main problems that is often encountered in the company's production activities which leads to the company's overall efficiency and profitability. PT. Health Today Indonesia is one of the companies experiencing this problem. Thus, this descriptive research with a quantitative approach aims to find solutions to these problems. Secondary data analysis from the 2013-2016 report uses the Economic Order Quantity (EOQ) calculation model from several divisions that are relevant to the 5 main products namely Fruit Smoothies, Bubble, Trisco, Honey and Sunfield. The results showed that the company was able to increase production efficiency, but this was not an actual condition due to externalities and the company's internal policy to delay the addition of purchases of raw materials and inventory, making the trend of inefficiency of the company's production decreased. Keyword:Economic Order Quantity, Inventory Management, Production